(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the effect of obesity on outcome of ventral hernia mesh repair. Study Design: It was a descriptive case series study Duration and Setting: This study was conducted at Surgical Units II & III, Chandka Medical College Hospital Larkana and Department of Surgery, Ghulam Muhammad Maher Medical College Hospital Sukkur from 01st November 2009 to 31th October 2011. Patients and Methods: A total of 113 patients of different age groups and both genders having different types of ventral herniae were included in the study. Body mass index (BMI) of all patients was recorded along with their demographic details to see its impact on outcome. Polypropylene mesh repair was performed using sublay technique under general anesthesia. Postoperatively patients were followed up for a period of one year for complications including seroma, haematoma, superficial wound infection, mesh infection and recurrence. Data analysis was carried out by using SPSS version 17. Results: Mean age was 50.26 years with female to male ratio of 4.8:1. Most common type of hernia remained Incisional (48.7%) followed by paraumbilical (31.0%), epigastric (11.5%) and umbilical (8.8%). BMI ranged from 23 to 43 with mean BMI of 28. 4 patients were morbidly obese. In 89.4% patients, there was single hernial defect and in 76% defect was < 4 cms. Mean operative time remained 67.093 minutes with average postoperative hospital stay of 4.8 days. Postoperatively 72.56% of patients recovered uneventfully. Most common complication was seroma (10.6%) followed by superficial wound infection (7%), mesh infection (4.4%), hematoma (2.65%) and recurrence (2.65%). Majority of patients who developed complications had BMI >30, majority of complications occurred in grade-I & II obesity group (79.8%). Conclusion: Obesity has a negative impact on outcome of ventral hernia mesh repair, therefore preoperative weight reduction is recommended in order to avoid complications.